Links betwee nthe prevalence of violence and the physical and emotional state of nursing profesionals working in supportive care and nursing - Jezukevičienė, Giedrė; Grigaliūnienė, Viktorija; Alčauskienė, Aurelija (Slauga. Mokslas ir praktika, 2022)
The aim of the present paper is to investigate the violence experienced by nursing professionals working in supportive care and nursing wards and the links to their physical and emotional state. A one-time anonymous standardised questionnaire was used for the research. The selected questionnaire was used to conduct research on workplace violence in the healthcare sector in various countries. The study involved 101 nursing professionals working in supportive care and nursing wards. An analysis of the survey data found that more than a third of nursing professionals said that the violence they experienced at work affected their physical condition. They felt sleep disturbances, blood pressure disorders, increased headaches, general fatigue. More than half of the study participants indicated that the psychological violence they experienced caused them internal tension, frustration with their profession, fear, anxiety, loss of self-esteem, and anger.